Strategies to increase the activity of microglia as efficient protectors of the brain against infections - Nau, Roland; Ribes, Sandra; Djukic, Marija; Eiffert, Helmut (Frontiers in Cellular Neuroscience, 2014)
In healthy individuals, infections of the CNS are comparatively rare. Based on the ability of microglial cells to phagocytose and kill pathogens and on clinical findings in immunocompromized patients with CNS infections, we hypothesize that an intact microglial function is crucial to protect the brain from infections. Phagocytosis of pathogens by microglial cells can be stimulated by agonists of receptors of the innate immune system. Enhancing this pathway to increase the resistance of the brain to infections entails the risk of inducing collateral damage to the nervous tissue. The diversity of microglial cells opens avenue to selectively stimulate sub-populations responsible for the defence against pathogens without stimulating sub-populations which are responsible for collateral damage to the nervous tissue. Palmitoylethanolamide (PEA), an endogenous lipid, increased phagocytosis of bacteria by microglial cells in vitro without a measurable proinflammatory effect. It was tested clinically apparently without severe side effects. Glatiramer acetate increased phagocytosis of latex beads by microglia and monocytes, and dimethyl fumarate enhanced elimination of human immunodeficiency virus from infected macrophages without inducing a release of proinflammatory compounds. Therefore, the discovery of compounds which stimulate the elimination of pathogens without collateral damage of neuronal structures appears an achievable goal. PEA and, with limitations, glatiramer acetate and dimethyl fumarate appear promising candidates.